Pengaruh Digital Marketing, Brand Image, Promotion Dan Kualitas Produk Terhadap Minat Beli Produk Kosmetik Make Over Di Kota Bengkulu - Fatricia, Sefhia Lara; Anggriani, Ida; Indriasari, Nia (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Today, people in Indonesia are in an increasingly sophisticated digital era. Technological advances have made many differences between the past and the present. One of the important things that has impacted the digital era is the use of product marketing activities, one of which is make over cosmetic products. The purpose of this study was to determine the effect of digital marketing, brand image, promotion and product quality on buying interest in make over cosmetic products in Bengkulu City. This type of research is a quantitative descriptive type of research. The data collection method in this study used a questionnaire technique, with a sample of 97 respondents. The results showed that multiple linear regression Y = 1.586 + 0.171 X1 + 0.464X2 + 0.043 X3 + 0.372 X4 + 1.464. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the variables Digital Marketing (X1), Brand Image (X2) Promotion (X3), Product Quality (X4) on buying interest in make over cosmetic products in Bengkulu City. The results of the digital marketing test (XI) show tcount 3.173> t table 1.660 and sigfinication 0.002 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that digital marketing has a positive and significant effect on buying interest in make over cosmetic products in Bengkulu City. The results of the brand image test (X2) show tcount 4.122> t table 1.660 and sigfinication 0.000 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that brand image has a positive and significant effect on buying interest in make over cosmetic products in Bengkulu City. The results of the promotion test (X3) show tcount 2.440> t table 1.660 and sigfinication 0.017 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that promotion has a positive and significant effect on buying interest in make over cosmetic products in Bengkulu City. The results of the product quality test (X4) show tcount 3.311> t table 1.660 and sigfinication 0.001 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that product quality has a positive and significant effect on buying interest in make over cosmetic products in Bengkulu City. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 11.859> 2.31, it is concluded that it accepts the hypothesis, meaning that there is a simultaneous influence between digital marketing (XI), brand image (X2), promotion (X3), product quality (X4) on buying interest in make over cosmetic products in Bengkulu City. This can be seen at a significance level of 0.000 <0.05.